IMPLEMENTASI METODE BOX-JENKINS UNTUK MEMPREDIKSI HARGA MINYAK DUNIA DAN PENGARUHNYA TERHADAP HARGA MINYAK INDONESIA - Desty Rakhmawati; Eka Tripustikasari (Jurnal Ilmiah Matematika dan Pendidikan Matematika (JMP), 2017)
Recently Indonesia's oil prices have declined despite oil consumption increases. The decline in Indonesia oil prices is affected by world oil prices. Therefore, the aim of this research is to predict WTI-type world oil price using Box-Jenkins method for non seasonal ARIMA modeling and how big does it influence to Indonesia oil price. WTI world oil price predictions for January to December 2017 are 54.17035, 54.89475, 55.12885, 55.20406, 55.22817, 55.23590, 55.23837, 55.23916, 55.23942, 55.23950, 55.23953, and 55.23953 dollars per barrels, respectively. Then the magnitude of the effect of WTI world oil prices to Indonesia oil prices is 1.735229 dollars per barrels.